Survivors : children's lives after the Holocaust - Clifford, Rebecca (Yale University Press, 2020)
"Told for the first time from their perspective, the story of children who survived the chaos and trauma of the Holocaust How can we make sense of our lives when we do not know where we come from? This was a pressing question for the youngest survivors of the Holocaust, whose prewar memories were vague or nonexistent. In this beautifully written account, Rebecca Clifford follows the lives of one hundred Jewish children out of the ruins of conflict through their adulthood and into old age. Drawing on archives and interviews, Clifford charts the experiences of these child survivors and those who cared for them--as well as those who studied them, such as Anna Freud. Survivors explores the aftermath of the Holocaust in the long term, and reveals how these children--often branded "the lucky ones"--had to struggle to be able to call themselves "survivors" at all. Challenging our assumptions about trauma, Clifford's powerful and surprising narrative helps us understand what it was like living after, and living with, childhoods marked by rupture and loss." --